Memories of Ups and Downs: The Vicissitudes of the Chongshansi in Taiyuan - Wen, Jing (Religions, 2022)
This article traces the erection of and changes in the Buddhist temple of Chongshansi in Taiyuan through the process of spatial production under the social background of the Ming and Qing Dynasties. It is stated that the founding time of the temple complies with the reorganization policies aimed at Buddhist institutions in the early Ming Dynasty, which confirms the setup of the Prefectural Buddhist Registry as the motivation for erecting the temple. Within the spatial structure of Taiyuan in the Ming Dynasty, its relative position with the Princely Palace of Jin (completed in 1375) and the expanded Taiyuan City is analyzed, revealing how its layout participated in the construction of the ritual path of Taiyuan under the control of the palace. The article concludes with a description of the fall of the temple following the loss of protection from the Jin Principality by tracing back its original form through the remains still evident in the city. The vicissitudes of the physical space of the temple are deeply connected to its role in the political space of the city. The article, thus, presents the changes in the temple throughout history. In positioning the temple back to the power and physical space of the imperial court, as well as the Jin Principality, a new perspective is provided into regional monasteries during the Ming Dynasty.